1996
DOI: 10.1063/1.116177
|View full text |Cite
|
Sign up to set email alerts
|

Valence-band discontinuities of wurtzite GaN, AlN, and InN heterojunctions measured by x-ray photoemission spectroscopy

Abstract: The valence-band discontinuities at various wurtzite GaN, AlN, and InN heterojunctions were measured by means of x-ray photoemission spectroscopy. A significant forward–backward asymmetry was observed in the InN/GaN–GaN/InN and InN/AlN–AlN/InN heterojunctions. The asymmetry was understood as a piezoelectric strain effect. We report the valence band discontinuities for InN/GaN=1.05±0.25 eV, GaN/AlN=0.70±0.24 eV, and InN/AlN=1.81±0.20 eV, all in the standard type I lineup. These values obey transitivity to withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
281
4
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 687 publications
(310 citation statements)
references
References 1 publication
22
281
4
3
Order By: Relevance
“…They then go on to match the experimentally observed results with an internal field of E int = 1.2 MV cm −1 , which compares to a theoretical value of E int = 2.5 MV cm −1 obtained by interpolating the piezoelectric and elastic constants from the binary values. 8 Recalculating these results using the p-i-n junction model, we get values of 49 and 1.5 nm for the depletion widths ͑corresponding to Ϫ10 and 3 V, respectively͒ and the flat band voltage of Ϫ14 V corresponds to a internal field of E int = 2.6 MV cm −1 , which is within 5% of the theoretical result.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…They then go on to match the experimentally observed results with an internal field of E int = 1.2 MV cm −1 , which compares to a theoretical value of E int = 2.5 MV cm −1 obtained by interpolating the piezoelectric and elastic constants from the binary values. 8 Recalculating these results using the p-i-n junction model, we get values of 49 and 1.5 nm for the depletion widths ͑corresponding to Ϫ10 and 3 V, respectively͒ and the flat band voltage of Ϫ14 V corresponds to a internal field of E int = 2.6 MV cm −1 , which is within 5% of the theoretical result.…”
supporting
confidence: 53%
“…This compares with 1.8 MV cm −1 obtained using the calculation when the material constants are obtained by interpolating the binary values. 8 A comparison of the experimental and calculated results for the amplitude of the measured peak absorption is shown in Fig. 4 and shows there is good agreement at high values of bias but poor agreement at low bias.…”
mentioning
confidence: 99%
“…Using c M =377 GPa, ci 2 =160 GPa, c 13 =114 GPa, c 33 =209 GPa [12], and s r =9.5 [6], we obtain d3i=-1.4xl0" 10 cm/V. Our value of d 3 i is almost the average value between a value of -0.9xl0" 10 cm/V obtained by Im et al [6] and -1.7x10"'° cm/V by Martin et al [13]. This value is also comparable with d33=2.0xl0" 10 cm/V as recently measured by Muensit et al using a laser interferometer [14].…”
supporting
confidence: 61%
“…The VB offset between GaN and InN has been measured in a number of studies. 4,[21][22][23][24][25][26][27][28] The most recent experimental study reported an offset of 0.58 ± 0.08 eV. 28 However, accurately measuring the offset is very difficult as seen from the wide spread (between 0.6 and 1.1 eV) of the reported experimental values.…”
Section: Alloys Ofmentioning
confidence: 99%